Knowledge and awareness of Palestinian health care professionals towards probiotics, prebiotics and synbiotics: a cross-sectional study from Palestine - Abdel Naser Zaid; Iyad Ali; Nidal Jaradat; Rowa Al Ramahi; Rula Hmeidat; Sanabil Nofal; Raneem Diab; Manwa Nasser; Heba Rabaya; Mohamed Tamimi; Ramzi Shawahni (Journal of Biological Research)
Probiotics are live microorganisms believed to confer health benefits when consumed appropriately. Prebiotics are non-digestible food components that promote health by encouraging the growth or activity of beneficial microorganisms. Synbiotics are a combination of probiotics and prebiotics. This study aimed to assess the knowledge and awareness of Palestinian healthcare professionals regarding probiotics, prebiotics, and synbiotics. A cross-sectional study was conducted across the West Bank using a structured questionnaire, and descriptive analysis was performed using SPSS. The results indicated that 68.5% of physicians and 83.4% of pharmacists were aware of probiotics, whereas only 37% of physicians and 48% of pharmacists had knowledge of prebiotics. Awareness of synbiotics was even lower, with only 20% of physicians and 26.6% of pharmacists reporting familiarity. These findings suggest that while there is a reasonable level of knowledge about probiotics, awareness of prebiotics and synbiotics is significantly lacking, which limits their use. Enhancing knowledge of these products could be facilitated through workshops, ongoing education, and the involvement of medical representatives.